E-government in Jordan and studying the extent of the e-government development index according to the United Nations report - Alqudah, Mohammad Ali; Muradkhanl, Leyla (Future Science / FSH-PH Publications, 2021)
This research paper presented the experiences of a group of countries as pioneering models in the field of e-government and compared them to Jordan with the aim of evaluating their status at the global and continental levels. Methods for measuring and evaluating the development of E-government suggested using a method called multi-practice are a practice of multi methodology, which combines methods and techniques, and proposes to evaluate the tangible and intangible benefits of e-government, which shows that the multiplicity of aspects of measurement may lead to a kind of reliability in e-government also Methods for measuring and evaluating e-government performance proposed by international organizations,By United Nations E-Government Survey The comparison and evaluation were done using the e-government maturity index issued by the United Nations EGDI, which includes the Telecommunication Infrastructure Index (TII) and The human capital Index (HCI), and the Online Service Index (OSI) e-government service sub-indicator, in the period between 2008 and 2020, and this comparison comes in order to benefit from these experiences, redress weaknesses, and exploit the opportunities available to Jordan to develop its e-government, keep pace with the global movement and raise its efficiency in a way that serves the goals of sustainable development The results were that Jordan, according to by United Nations E-Government Survey Jordanian e-government is still in the first generation It has many improvements performance on the e-government index the change in the EGDI . Some comparisons of Jordan with Arab countries have been presented in the EGDI in 2020 for the United Nations report